Pre-schoolers’ Interest and Caring Behaviour Around a Humanoid Robot - Ioannou, Andri; Andreou, Emily; Christofi, Maria (My University, 2015)
This exploratory case study involved a humanoid robot, NAO, and four pre-schoolers. NAO was placed in an indoor playground together with other toys and appeared as a peer who played, talked, danced and said stories. Analysis of video recordings focused on children’s behaviour around NAO and how the robot gained children’s attention and interest. First, the study demonstrated that pre-schoolers easily interact with this humanoid robot and showed particular interest to NAO when he danced and when he was in need of help (e.g., fell down) demonstrating caring behaviour such as kisses, hugs and cuddling. Further, the study contributes a systematically developed coding scheme capturing the verbal and non-verbal behaviour of young children around NAO.
Keywords: Caring behaviour; Coding scheme; Humanoid robot; Interaction; Interest; NAO; Preschool